LOMBA BERWUDHU SEBAGAI MEDIA PEMBINAAN IBADAH ANAK SEKOLAH DASAR OLEH MAHASISWA KKN STITNU SAKINAH DHARMASRAYA DI MASJID AL-JAMIK NAGARI AMPALU: Penelitian Deskriptif - Rahmadani; Hardia Y, Desvita; Putri, Rahmadini; Fitriana, Veoretta; Adillah, Suci (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Wudu Practice Competition is one of the worship development activities carried out by the KKN students of STITNU Sakinah Dharmasraya at Al-Jamik’ Mosque. This study aims to describe the implementation of the competition, analyze its effectiveness on improving the religious practice understanding of elementary school children, and examine its relevance to Islamic education theory. The research employed a descriptive qualitative approach based on observation, documentation, and literature review from ten national journals. The results show that the wudu practice competition has a positive impact on enhancing children’s understanding, skills, and manners in performing wudu. In addition, the activity fosters motivation, builds confidence, and strengthens the participants’ religious character. Thus, the wudu practice competition can serve as an effective, engaging, and practical model for worship development among elementary school students.